Evaluación del impacto de las políticas públicas del buen vivir en organizaciones agroproductivas solidarias de los cantones Bolívar y Pichincha - Cedeño Sánchez, Mónica Mercedes (2019)
The purpose of the titling work is to evaluate the impact of the public policies of the National Plan of Good Living 2013-2017 for the verification of their fulfillment in the Solidarity Agroproductive Organizations (OAPS) of Bolívar and Pichincha cantons. The techniques used were the theoretical and conceptual bases on the subject of study, which diagnosed the current situation of the OAPS and the PEA control group, making necessary to select indicators in the measurement of the impact in the organizations. Finally, the comparison of the level of execution of public policies in the associates and their impact on non-associated ones. Methodologically, the inductive method was used to analyze the different situations of those involved to obtain a broad knowledge of the problem, as well as deductive research that facilitated a generalized notion of the causes of the behavior of public policies; among other methods, it was presented the synthetic analytic to understand the decomposition of ideas coming from different authors and to carry out the purification of the indicators, leaving the opportune ones for the investigation. As a tool, a questionnaire based on dichotomous and multiple-choice questions was used according to the three harmonies of good living; internal harmony, with the community and with nature. To base the results, it was necessary to apply an SPSS software program that facilitated the interpretation of the desired results, where from the 24 questions selected, 20 were do not comply in Bolívar canton and 21 in Pichincha.